Design of a Foreigner Registration System at the TPI Depok Immigration Office - Shouqi Denanto; Sharyanto Sharyanto; Bernadus Gunawan Sudarsono (Yayasan Bina Internusa Mabarindo, 2022)
Immigration Office Class I Non TPI Depok is a government agency, engaged in services related to immigration. Some of the services provided by the Immigration Office to the public are services for foreigners. The foreigner registration process at the Class I Non TPI Depok immigration office is still done manually and the registration results take too long and searching for files that have been archived is quite time-consuming. The design method used is the Unfield Modeling Language (UML) programming language PHP and MySQL as the database. and testing using blackbox. It is hoped that the creation of a web-based Foreign National Registration System can help all parties involved in the process and avoid mistakes.